2019
DOI: 10.1016/j.chempr.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Bambusurils as Highly Effective and Selective Transmembrane Cl−/HCO3− Antiporters

Abstract: ArticleFluorinated Bambusurils as Highly Effective and Selective Transmembrane Cl À /HCO 3 À Antiporters Synthetic anion receptors can be used to transport ions across membranes. In this work, bambusuril macrocycles are demonstrated to be very efficient in exchanging chloride and bicarbonate ions, whereas exchange with nitrate is much slower. This is explained by the anion binding properties of the receptor. The high rates of transport by these bambusurils and mechanistic insight provided here represent an adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
176
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(188 citation statements)
references
References 68 publications
12
176
0
Order By: Relevance
“…It has been proposed by A.P. Davis, [20] us, [10c] and Valkenier [21] that the lack uniport activity may be due to strong binding of anion transporters to either Clions from the solution or lipid phosphate headgroups at the water-lipid interface thus inhibiting the diffusion of free transporters, and this effect is shown here to result in voltage-dependent H + /Clsymport. However, it remains unclear whether Clbinding or headgroup binding is responsible because of unavailability of experimental evidence supporting either hypothesis.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…It has been proposed by A.P. Davis, [20] us, [10c] and Valkenier [21] that the lack uniport activity may be due to strong binding of anion transporters to either Clions from the solution or lipid phosphate headgroups at the water-lipid interface thus inhibiting the diffusion of free transporters, and this effect is shown here to result in voltage-dependent H + /Clsymport. However, it remains unclear whether Clbinding or headgroup binding is responsible because of unavailability of experimental evidence supporting either hypothesis.…”
Section: Resultsmentioning
confidence: 65%
“…It should be noted the above conclusion might not be applicable to extremely strong Clreceptors (with Claffinity of > 10 10 M -1 in MeCN) recently reported. [21] As summarised in Table 1, we have demonstrated that the five synthetic anion transporters and prodigiosin can be classified into three categories with fundamentally different transport mechanisms regarding the occurrence of uniport and voltage-dependence. In a separate study, we re-examined the bisurea type of anion transporters [9] and found a "non-uniport" mechanism for all bisureas compounds identical to the mechanism of 2 and 4.…”
Section: Resultsmentioning
confidence: 89%
“…It should be noted the above conclusion might not be applicable to extremely strong Cl − receptors (with Cl − affinity of > 10 10 M -1 in MeCN) recently reported. [23] As summarised in Table 1, we have demonstrated that the five synthetic anion transporters and prodigiosin can be classified into three categories with fundamentally different transport mechanisms regarding the occurrence of uniport and voltage-dependence. Notably, adding electron-withdrawing cyano groups to 3 in an attempt to improve the anion transport efficiency (i.e.…”
Section: Resultsmentioning
confidence: 89%
“…[12][13][14][17][18][19] A series of compounds that was shown to function efficiently as Cl − /HCO 3 − exchanging anionophores, but without employing N-H based H-bond donors, are the fluorinated bambus [6]urils. 24 These macrocyclic receptors have an electron deficient cavity formed by twelve (polarised) methine C-H groups, which leads to exceptionally high affinity constants in the range of 10 7 -10 11 M -1 in acetonitrile for HCO3 − , Cl − , and NO3 − , despite the absence of acidic protons. Other anionophores employing C-H groups for anion recognition were, however, unable to transport HCO3 − .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, a halide-sensitive fluorescent probe, such as lucigenin or SPQ, is encapsulated in liposomes and the influx (or efflux) of Cl − is monitored via the quenching of the fluorescence. 12,20,24,25,38 This is again an indirect method to study the transport of HCO3 − , which is assumed to balance the charge from the influx of Cl − if transport is observed. A third indirect method to monitor transport of HCO3 − is by the recently reported osmotic assay, where the efflux of HCO3 − by an anionophore is accompanied by the efflux of a cation (by a cationophore), resulting in an osmotic efflux of water, that can be observed as a change in the scattering intensity of the liposome dispersion.…”
Section: Introductionmentioning
confidence: 99%